Drug-drug interactions of tacrolimus - Rančić Nemanja K.; Vavić Neven N.; Kovačević Aleksandra M.; Mikov Momir M.; Dragojević-Simić Viktorija M. (Srpsko lekarsko drustvo, 2015)
Introduction: Tacrolimus, potent immunosupressive drug, has large inter- and intraindividual pharmacokinetic variability. The aim: The aim of this current topic is to describe the importance of tacrolimus drug-drug interactions. Pharmacokinetic interactions between tacrolimus and other drugs: Concerning the fact that it is also a medicine with the narrow therapeutic range, its interactions with other drugs mediated by both P-glycoprotein and CYP3A enzymes are potentially very important. Conclusion: Interactions between tacrolimus and other drugs leading to overexposure to tacrolimus is connected with significant toxicity, while the subtherapeutic blood concentrations increase the probability of transplanted organ rejection.